Physiology of Leymus chinensis under seasonal grazing: Implications for the development of sustainable grazing in a temperate grassland of Inner Mongolia. (1st October 2020) - Song, Liangyuan; Pan, Yan; Gong, Jirui; Li, Xiaobing; Liu, Min; Yang, Bo; Zhang, Zihe; Baoyin, Taogetao
Abstract: Plants have different physiological characteristics as the season changes, grazing management in compliance with plant growth and development characteristics may provide new ideas for sustainable livestock development. However, there has been little research on seasonal grazing and plants physiological responses under it. Here, we studied a typical steppe ecosystem of Inner Mongolia, with Leymus chinensis as the dominant species, in five grazing treatments: continuous grazing, seasonal grazing (which started in spring or in early and late summer), and no grazing (the control). We analyzed growth and resistance of L. chinensis in the five treatments by measuring annual primary productivity, morphological traits and various physiological processes. Compared with continuous grazing, seasonal grazing significantly alleviated grassland degradation. The plants were less affected by stress under spring grazing, with net photosynthesis and non-photochemical quenching closer to the control values and with a lower malondialdehyde content. The annual primary production of plants under grazing started in the early and late summer were 3–4 times the value under continuous grazing. Regrowth under early-summer grazing was greatly improved, and stress resistance was stronger with a higher proline content and high antioxidant enzyme activity. And nutrient accumulation at the end of the growing season such as abundant soluble sugars were transferred from aboveground tissue to the roots in September under late-summer grazing, which benefited regrowth the next year. All these physiological processes were regulated by hormonal changes. Our results highlight how plants response grazing stress in different growing seasons and suggest that seasonal grazing can improve the stress resistance and regrowth capacity of forage vegetation, and applying this knowledge can promote more sustainable grazing practices. Highlights: Plants adjusted its Morphological and physiological traits in response to grazing ➢ Plant regrowth in the next year affected by nutrient accumulation and transfer. Different responses of plants under grazing were regulated by various hormones. Seasonal grazing alleviated grazing stress and promote regrowth of plants. Grazing started in June was the most suitable grazing regime for production.